Apontamentos sobre a tragédia moderna nas peças Death of a Salesman [A morte do caixeiro viajante] de Arthur Miller e A moratória de Jorge Andrade - Rocha, Andréa Aparecida (2018)
Basead on the form of modern tragedy, the present research is devoted to analyzing the plays of Death of Salesman (1949), the american playwright Arthur Miller (1915 - 2005), and A Moratória (1955) by brazilian playwright Jorge Andrade (1922 – 1984), relying on the form of modern tragedy, and based on both texts, that is, on theatrical texts and their respective dramatic reflective content. These dramas demonstrate that both Miller and Andrade shared the same concern, proposing conflicts based on historical crises, in order to highlight the struggle of the common man against society, through the daily lives of two patriarchs and their families, who are displaced with the social and economic expansion of the mid-twentieth century. To understand these and other issues and how they are inserted dramaturgically, this study is organized as follows: the first chapter contextualizes historically the tragedy to its modern condition, after the influence of the drama and its crisis, with the purpose of arriving at the discussion about the tragedy and its liberal condition acquired in contemporaneity. The second chapter presents the life and work of both playwrights, followed by initial considerations about the plays in question and their respective historical contexts. The third and last chapter, however, compares and analyzes relevant aspects of both texts, such as: father-son conflict, representation of women, protagonists as modern heroes, of the houses as the background of dramatic actions and formal scenic resources that give expressiveness to the concerns and subjective reality experienced by the characters.